Increasing Public Participation in the 2024 Elections: A Stakeholders Mapping Analysis Approach - Denny Iswanto; Dewi Bayu Pamungkas (Journal of Transformative Governance and Social Justice, 2023)
In the context of the successful implementation of the 2024 General Election it is necessary to have the synergy of Stakeholders/stakeholders from all groups involved. Stakeholders have a role to play in realizing better democracy, one of which is through increasing people's political participation in the midst of situations and conditions that are still in the recovery period due to the Covid-19 Pandemic. The existence of this problem requires concrete new steps in dealing with this unusual situation by maximizing the role of stakeholders. The purpose of this study is to map the roles of various stakeholders involved in maximizing the role of each actor in building synergy in the implementation of elections which directly or indirectly affect the level of community political participation in the. This study uses a type of qualitative research using secondary data analysis techniques in writing. The results of the stakeholder mapping show that the central and local governments are the contest setters, KPU, Bawaslu, NGOs, the media and political parties as players, candidates and pairs of candidates are designated as subjects, and the voting public as crowds. With the stakeholder mapping in the 2024 Election, this can be used as a strategic policy step to increase public political participation in the 2024 Election.